The abandoned übervater: Max Weber and the neoliberals - Stefan Kolev (Duke University, Center for the History of Political Economy (CHOPE), 2018)
This paper addresses the intellectual relationship between Max Weber and three key proponents of neoliberalism: F.A. Hayek, Walter Eucken and Wilhelm Röpke. This relationship is contextualized in the history of German-language political economy, focusing on the nexus and proximity between early 20th century economic sociology and the emergence and evolution of the various neoliberal political economies from the 1930s onwards. While during his lifetime Weber was a towering scholarly and public figure recognized well beyond the German-language area, after his passing in 1920 he successively fell into oblivion, also for the neoliberal generation at the heart of the paper who started publishing in the immediate aftermath of Weber's age. The structure of the paper is tripartite. In section 2, traces of Weber in the neoliberal writings are collected, starting with an instrumental digression to Ludwig von Mises's treatment of Weber. Mises as well as the neoliberals focused on Weber's legacy in epistemology, methodology and economic history, while references to his sociological contributions are seldom and unsystematic. In section 3, central commonalities between Weber's economic sociology and the political economies of Hayek, Eucken and Röpke are outlined. In section 4, six hypotheses are formulated to tentatively explain the cursory and declining appreciation of Weber by the neoliberals during their lifetime.
Keywords: A11; B25; B31; P16; Z13; 330; Max Weber; F.A. Hayek; Walter Eucken; Wilhelm Röpke; Ludwig von Mises; neoliberalism; ordoliberalism; economic sociology